Immunomodulating medicine Galavit antitumor action research - L. I. Primushko; V. M. Semenova; А. N. Lisyany; A. I. Tormasova; L. P. Stayno (Ukrainian Neurosurgical Journal, 2007)
Galavit cytotoxic and antiprolipherating action on the brain glial tumors in vitro was studied. Galavit as well as Cisplatin brakes glioblastoma and medulloblastoma cells proliferation in two–three times, and in one and a half time — cells of astrocytoma.Galavit, that was giving to rats with experimental glioma 101.8, led to lifespan lengthening as well as necrotic changes in tumor.Galavit is suggested for brain gliomas treatment.